Ontogeny of CYP3A and UGT activity in preterm piglets: a translational model for drug metabolism in preterm newborns - Buyssens, Laura; Valenzuela, Allan; Prims, Sara; Ayuso, Miriam; Thymann, Thomas; Van Ginneken, Chris; Van Cruchten, Steven (Frontiers in Pharmacology, 2023)
Despite considerable progress in understanding drug metabolism in the human pediatric population, data remains scarce in preterm neonates. Improving our knowledge of the ADME properties in this vulnerable age group is of utmost importance to avoid suboptimal dosing, which may lead to adverse drug reactions. The juvenile (mini)pig is a representative model for hepatic drug metabolism in human neonates and infants, especially phase I reactions. However, the effect of prematurity on the onset of hepatic phase I and phase II enzyme activity has yet to be investigated in this animal model. Therefore, the aim of this study was to assess the ontogeny of CYP3A and UGT enzyme activity in the liver of preterm (gestational day 105 – 107) and term-born (gestational day 115 – 117) domestic piglets. In addition, the ontogeny pattern between the preterm and term group was compared to examine whether postconceptional or postnatal age affects the onset of enzyme activity. The following age groups were included: preterm postnatal day (PND) 0 (n = 10), PND 5 (n = 10), PND 11 (n = 8), PND 26 (n = 10) and term PND 0 (n = 10), PND 5 (n = 10), PND 11 (n = 8), PND 19 (n = 18) and PND 26 (n = 10). Liver microsomes were extracted, and the metabolism of CYP3A and UGT-specific substrates assessed enzyme activity. Preterm CYP3A activity was only detectable at PND 26, whereas term CYP3A activity showed a gradual postnatal increase from PND 11 onwards. UGT activity gradually increased between PND 0 and PND 26 in preterm and term-born piglets, albeit, being systematically lower in the preterm group. Thus, postconceptional age is suggested as the main driver affecting porcine CYP3A and UGT enzyme ontogeny. These data are a valuable step forward in the characterization of the preterm piglet as a translational model for hepatic drug metabolism in the preterm human neonate.